Sternal resection of a solitary renal cell carcinoma metastasis: a case report and a literature review - Čerškutė, Minija; Kinčius, Marius; Januškevičius, Tomas; Cicėnas, Saulius; Ulys, Albertas (Acta medica Lituanica, 2019)
Background. Renal cell carcinoma (RCC) may be metastatic, although solitary sternal metastasis of RCC is a rare medical condition. Here we report an unusual case of a 63-year-old male with a solitary sternal metastasis as an initial presentation of clear-cell renal cell carcinoma. Materials and methods. A 63-year-old male presented with a small sternal mass. Chest computer tomography (CT) and a biopsy from the sternal tumour were performed. Histopathological examination revealed the diagnosis of renal clear cell carcinoma metastasis to the sternal bone. On the basis of a subsequently performed abdominal CT the patient was confirmed with a suspicion of a left renal lower pole tumour. Treatment with sunitinib was initiated. Due to the limited response and a growing sternal mass, the patient was admitted to the National Cancer Institute after two cycles of sunitinib therapy. Open left partial nephrectomy was performed followed by the resection of the sternal metastasis two months later. The chest wall was reconstructed with polypropylene mesh combined with transversal rectus abdominis musculocutaneous flap. Results. The postoperative course after the partial nephrectomy was uneventful. The postoperative course of metastasectomy complicated with the right pneumothorax which was successfully treated by insertion of a chest tube. Bleeding from the upper digestive tract also occurred on the seventh postoperative day but was successfully controlled by haemostasis with three 20 ml endoscopic injections of 1:10,000 solution of epinephrine. The patient had been followed up after the surgery for 30 months with biannual chest and abdominal CT scans that showed neither local nor distant recurrence of the disease. Conclusions. Radical surgical treatment of a solitary renal clear cell carcinoma metastasis may offer the best cancer-specific outcomes and improve the quality of life in some patients.